Food Standards are Good – for Middle-Class Farmers - Henrik Hansen; Neda Trifković (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2013)
We estimate the causal effect of food standards on Vietnamese pangasius farmers' wellbeing measured by per capita consumption expenditure. We estimate both the average effects and the local average treatment effects on poorer and richer farmers by instrumental variable quantile regression. Our results indicate that large returns can be accrued from food standards, but only for the upper middle-class farmers, i.e., those between the 50% and 85% quantiles of the expenditure distribution. Overall, our result points to an exclusionary impact of standards for the poorest farmers while the richest do not apply standards because the added gain is too small.
Keywords: Q13; Q18; D02; D13; D31; 330; food standards; pangasius; instrumental variable; quantile regression; Vietnam; Asia